Synthesis and Characteristics of Nano Crystalline LiAlxMn2-xO4 Cathode Material Using Solid State Combustion Method for Li-ion Batteries - Sheela Vimala Rani1, A.; Lalitha1, S.; Gangadharan2, R. (Asian Journal of Chemistry, 2013)
Lithium-ion batteries are most advanced batteries used for modern portable electronic devices such as mobile phones, notebook computers and camera recorders. They are also big potential for lithium-ion batteries to be used for electric vehicles, hybrid electric vehicles and stationary power storage. In particular, the later will bring a significant contribution to reduce green house gas emissions, global warming and climate change. Materials research is a key role in the development of next generation of advanced lithium-ion batteries with high energy density, high power density and long cycle life. LiMn2O4 has been emerging as a new cathode material for lithium ion batteries with low cost. But it suffers from loss of capacity during cycling. To improve the cycle performance of spinel LiMn2O4, Al doped LiMn2O4 powders are synthesized. A simple solid state combustion method has been tried for the preparation of nano particle size LiAlxMn2-xO4 powder with urea as the igniter and glycerol as the binding material. LiNO3, Al(NO3)3 and Mn(NO3)3 were mixed together to form a homogeneous paste. This paste was carefully heated to 100 ºC in the muffle furnace and then the product is heated to 800 ºC for 12 h. The obtained nano powder was subjected to XRD, TEM, TG/DTA and FTIR analysis. The particle size of the material was roughly calculated from the X-ray data using Scherrer equation. The TEM analysis was carried out in detail to confirm the particle size.